Pengelolaan Iklim Sekolah Yang Efektif Dalam Menunjang Kinerja Guru di Sekolah Dasar Negeri 028354 Binjai - Alberto Maradona Sitepu; Emilda Sulasmi (UMSU, 2023)
This research aims to determine effective school climate management in supporting teacher performance at State Elementary School 028354 Binjai. Managing school climate by building harmonious relationships between teachers, staff and students so that it can motivate students to learn better at school. In managing a good social environment at school to support teacher performance and learning, namely by implementing school programs. The principal manages a conducive school climate, where the principal in managing the school climate includes (1) personnel placement, (2) fostering relationships and communication, (3) teacher dynamics, (4) conflict resolution, (5) collecting and utilizing information, (6) Enrichment and completeness of facilities and infrastructure for the working environment and learning environment.